Influence of Cryogenic Treatment and Tempering Temperature on Microstructural Evolution and Dry Sliding Wear Behavior of AISI D3 Cold-Work Tool Steel - Boztepe, Alican; Gecu, Ridvan (ASME, 2025)
AISI D3 cold-work steel was shallow and deep cryogenically treated and double-tempered at 150, 250, and 350 degrees C temperatures. Cryogenic processes transformed the retained austenite into martensite, while double tempering produced Fe-, Cr-, and W-rich carbides. The wear losses of cryogenically treated specimens decreased by up to 60% compared to conventionally heat-treated samples. Worn surfaces mainly experienced abrasive and adhesive wear mechanisms. Due to the formation of homogeneously dispersed fine carbides at 250 degrees C, oxidative wear occurred at the matrix phase, resulting in the lowest wear rate. The samples tempered at 150 degrees C suffered from the severe abrasive action of hard carbide particles, while the samples treated at 350 degrees C failed because of carbide coarsening.
Keywords: cryogenic treatment; wear; AISI D3; cold-work steel; double tempering; hardness; sliding; wear mechanisms; HEAT-TREATMENT; CORROSION; RESISTANCE; D2; Engineering